Nutrient composition of Rana galamensis - N.O, Muhammad; Ajiboye, B.O. (Global Journal of Food and Agribusiness Management, 2011)
The proximate composition, amino acid, fatty acid and mineral profiles of Rana galamensis were investigated. The results of the proximate analysis revealed that R. galamensis has high level of protein (53.74 ± 0.89) with considerable amount of lipid (9.52 ± 0.31) and very low fibre content. The amino acid profile showed that it contains seventeen amino acids with nine indispensable amino acids being higher than those recommended by WHO/FAO reference; the ether extract from R. galamensis contains four common fatty acids, lauric acid, palmitic acid, stearic acid and linoleic acid. The result also revealed that R. galamensis is a good source of dietary minerals especially selenium, calcium and phosphorous. R. galamensis is therefore considered to be a rich source of essential nutrients that would be useful for both animal and human